Health-care professionals’ perceptions of interacting with patients of South Asian origin attending early inflammatory arthritis clinics - Kumar, Kanta (Rheumatol Adv Pract, 2019)
OBJECTIVE: The aim was to explore the perceptions of rheumatology health-care professionals (HCPs) of interacting with patients of South Asian origin attending early inflammatory arthritis clinics. METHODS: We used face-to-face semi-structured interviews, designed in partnership with a clinician partner, to interview 10 HCPs involved in the running of early inflammatory arthritis clinics across seven centres in the UK. Data were recorded, transcribed by an independent company and analysed using inductive thematic analysis. RESULTS: Three emerging themes were identified that characterized consulting experiences of HCPs: varied approaches were used in early inflammatory arthritis clinic; the challenges for rheumatology HCPs in managing and delivering information to patients of South Asian origin in early inflammatory arthritis clinics; and moving towards good practice, the views on managing future patients of South Asian origin in early inflammatory arthritis clinics. Overall, HCPs found that they required additional skills to support the engagement and management for patients of South Asian origin living with inflammatory arthritis. The HCPs felt that they were less effective in addressing self-management issues for this patient group, and they found it difficult to determine adherence to medication. In such consultations, HCPs perceived that their own limitation of inadequate training contributed towards poor consultations. CONCLUSION: For the first time, our data demonstrate that the management of patients of South Asian origin in early inflammatory arthritis clinics is under-served. To address this, HCPs have identified training needs to improve knowledge and skills in engaging with and supporting patients of South Asian origin. These findings provide a good direction for future research.